2018
DOI: 10.1002/ece3.4296
|View full text |Cite
|
Sign up to set email alerts
|

Landscape genetics identifies streams and drainage infrastructure as dispersal corridors for an endangered wetland bird

Abstract: Anthropogenic alterations to landscape structure and composition can have significant impacts on biodiversity, potentially leading to species extinctions. Population‐level impacts of landscape change are mediated by animal behaviors, in particular dispersal behavior. Little is known about the dispersal habits of rails (Rallidae) due to their cryptic behavior and tendency to occupy densely vegetated habitats. The effects of landscape structure on the movement behavior of waterbirds in general are poorly studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 88 publications
(134 reference statements)
1
6
0
Order By: Relevance
“…Gallinules had the highest residency to a single wetland (0.93 average residency), although gaps in time when birds were not detected (range = 2–25 days) suggest occasional movement of birds outside of the monitored wetlands. The lack of detected movement found in our study are consistent with mark‐recapture studies on Hawaiian gallinules and population genetic studies that reported moderate to strong genetic structuring between wetlands, even between wetlands close to one another (Sonsthagen et al 2018, van Rees et al 2018 a , b , c ). On the other hand, large, continuous wetlands (e.g., Hamakua Marsh, James Campbell NWR) on Oʻahu had evidence of higher gene flow among sampled locations, indicating gallinules will move between wetlands if there is habitat connecting wetlands (van Rees et al 2018 c ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Gallinules had the highest residency to a single wetland (0.93 average residency), although gaps in time when birds were not detected (range = 2–25 days) suggest occasional movement of birds outside of the monitored wetlands. The lack of detected movement found in our study are consistent with mark‐recapture studies on Hawaiian gallinules and population genetic studies that reported moderate to strong genetic structuring between wetlands, even between wetlands close to one another (Sonsthagen et al 2018, van Rees et al 2018 a , b , c ). On the other hand, large, continuous wetlands (e.g., Hamakua Marsh, James Campbell NWR) on Oʻahu had evidence of higher gene flow among sampled locations, indicating gallinules will move between wetlands if there is habitat connecting wetlands (van Rees et al 2018 c ).…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, large, continuous wetlands (e.g., Hamakua Marsh, James Campbell NWR) on Oʻahu had evidence of higher gene flow among sampled locations, indicating gallinules will move between wetlands if there is habitat connecting wetlands (van Rees et al 2018 c ). Indeed, at a landscape level, current genetic structuring of gallinules on Oʻahu is best explained by connectivity through waterways (e.g., streams, drainage ditches), which were abundant in the intervening matrix between wetlands (van Rees et al 2018 b ). In the closely related Mariana common moorhen ( Gallinula chloropus guami ), individual birds frequently moved among permanent and ephemeral wetlands between wet and dry seasons, and rapidly colonized a new island (≥70 km dispersal) when new habitat was created (Takano and Haig 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Green stormwater infrastructure practices also create urban freshwater habitats that support local wildlife [91,92]. In Hawai'i, urban stormwater NBS like drainage swales and ditches provide not only habitat, but facilitate landscape-scale movements and enhanced population connectivity in an endangered waterbird [93]. Such contributions not only to total habitat but also landscape connectivity could support biodiversity in urban wetlands.…”
Section: Improve Water Qualitymentioning
confidence: 99%
“…The land cover map was converted to a binary surface with two classes: Forest and Non-Forest. In some cases, analysis of binary habitat-non habitat surfaces can provide complementary or novel insights compared with the analysis of multi-variable surfaces (van Rees et al, 2018;Van Strien et al, 2012).…”
Section: Isolation By Resistance and Distancementioning
confidence: 99%